Distinct trajectories of psychological distress among resettled refugees: Community acceptance predicts resilience while low ingroup social support predicts clinical distress. (February 2023) - O'Donnell, Alexander W.; Paolini, Stefania; Stuart, Jaimee
Refugees can experience elevated levels of psychological distress upon resettlement, although disparate outcomes over time are expected. The current study modeled trajectories of changes in distress over a 5-year period among resettled refugees and sought to explicate post-settlement factors that influence distress over time. A large-scale sample of refugees resettled in Australia (2, 399) was tracked over a 5-year period, completing measures of psychological distress at each wave and initial risk and protective factors immediately after resettlement. A latent class growth analysis conducted on distress found four unique classes characterized by (1) resilient levels of distress, (2) consistent clinical distress, (3) recovering levels of distress, and (4) deteriorating distress. Lower perceived discrimination and greater positive context of reception predicted membership to the resilient group and differentiated the recovering and deteriorating groups. Further, lower ingroup social support predicted membership to the clinically distressed group relative to all others. We conclude by echoing calls to strengthen community support for refugees and promote ingroup ties, particularly among those who are the most vulnerable.